A facile method to compare EFTEM maps obtained from materials changing composition over time. Issue 12 (31st October 2015) - Casu, Alberto; Genovese, Alessandro; Di Benedetto, Cristiano; Lentijo Mozo, Sergio; Sogne, Elisa; Zuddas, Efisio; Falqui, Andrea
ABSTRACT: Energy Filtered Transmission Electron Microscopy (EFTEM) is an analytical tool that has been successfully and widely employed in the last two decades for obtaining fast elemental maps in TEM mode. Several studies and efforts have been addressed to investigate limitations and advantages of such technique, as well as to improve the spatial resolution of compositional maps. Usually, EFTEM maps undergo post‐acquisition treatments by changing brightness and contrast levels, either via dedicated software or via human elaboration, in order to maximize their signal‐to‐noise ratio and render them as visible as possible. However, elemental maps forming a single set of EFTEM images are usually subjected to independent map‐by‐map image treatment. This post‐acquisition step becomes crucial when analyzing materials that change composition over time as a consequence of an external stimulus, because the map‐by‐map approach doesn't take into account how the chemical features of the imaged materials actually progress, in particular when the investigated elements exhibit very low signals. In this article, we present a facile procedure applicable to whole sets of EFTEM maps acquired on a sample that is evolving over time. The main aim is to find a common method to treat the images features, in order to make them as comparable as possible without affecting the information there contained. Microsc. Res. Tech. 78:1090–1097, 2015 . © 2015 Wiley Periodicals, Inc.